2021
DOI: 10.3390/cells10123346
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Immune Response Profile of Tumor-Draining Lymph Nodes after High-Intensity Focused Ultrasound Ablation of Breast Cancer Patients

Abstract: Previous studies have revealed that high-intensity focused ultrasound (HIFU) ablation can trigger an antitumor immune response. The aim of this study was to investigate immune response in tumor-draining lymph nodes (TDLNs) after HIFU treatment. Forty-eight female patients with biopsy-confirmed breast cancer were divided into a control group and an HIFU group. In the control group, 25 patients underwent modified radical mastectomy, but 23 patients in the HIFU group received HIFU ablation of primary cancer, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Upon HIFU, the authors investigated the immune response efficacy and the ability of HIFU to induce the secretion of several cytotoxic factors (FasL, Perforin, and GranzymeB in ALNs). This study revealed that HIFU stimulates an effective immune response by infiltration of key immune cell subsets, such as CD4+ T and CD57+ T cells, with a concomitant secretion of cytotoxic factors that contrast the further diffusion of metastatic breast cancer cells present in the ALNs [22].…”
Section: Radiotherapy and Tumor Ablation: First-line Tools To Contras...mentioning
confidence: 89%
“…Upon HIFU, the authors investigated the immune response efficacy and the ability of HIFU to induce the secretion of several cytotoxic factors (FasL, Perforin, and GranzymeB in ALNs). This study revealed that HIFU stimulates an effective immune response by infiltration of key immune cell subsets, such as CD4+ T and CD57+ T cells, with a concomitant secretion of cytotoxic factors that contrast the further diffusion of metastatic breast cancer cells present in the ALNs [22].…”
Section: Radiotherapy and Tumor Ablation: First-line Tools To Contras...mentioning
confidence: 89%
“…The study showed that in the HIFU group, axillary LN had a greater immune reaction than in the control group (100% vs 64%). 71 A phase I clinical trial by the University of Virginia is currently underway to examine the combination of Pembrolizumab either before or after HIFU, in patients with advanced/metastatic BC (R). 72 Complete response was 64.8% in the pembrolizumab-chemotherapy group and 51.2% in the placebo-chemotherapy group.…”
Section: Breast Cancer Ablation and Immunotherapymentioning
confidence: 99%
“…After HE and immunohistochemical analysis of axillary lymph nodes, HIFU was observed to stimulate the immune responses of the whole body and significantly increase the number of effector T cells, activated CTLs, and NK cells. [ 124 ]…”
Section: Clinical Physiotherapy‐activated or Combined Immunotherapymentioning
confidence: 99%